Fiscal policy for decarbonization of energy in Europe - Robinson, D (Oxford Institute for Energy Studies, 2017)
Decarbonization policy has focused thus far on low hanging fruit, especially energy efficiency and renewables. Attention will need to move to other sectors, especially transport and buildings, which together account for about 60% of energy-related carbon emissions in the EU. Consumers will be active participants and at the centre of this energy transition. This reinforces the importance of minimizing energy pricing distortions, including those due to fiscal policy. This report argues that fiscal policy may act as a barrier to the decarbonisation of transport and buildings. This is due to levies on electricity that have risen substantially since 2008, primarily but not exclusively to finance renewable power development whose costs could not be recovered through markets. The higher the penetration of renewable energy, the higher the levies on electricity and the less competitive it becomes by comparison to the fossil fuels. The report also argues that, even if the fiscal policy barrier were eliminated, electrification would be only one competing option among others. The report proposes guidelines for energy sector fiscal reform that will be aligned with efficient decarbonisation Fiscal policy should, inter alia: be technology neutral after internalizing environmental externalities; finance the extra cost of renewables and other public goods through government taxation raised in the least distorting ways consistent with distributional objectives; and be part of a comprehensive revenue-neutral fiscal reform. Fiscal policy is only one of the policy instruments that governments have at their disposal and it is often not the most important one. However, fiscal reform is a relatively easy and quick way of starting to move in the right direction and of reducing the risk of getting stuck with the wrong sort of investment that will lock in high carbon intensity.